Safety evaluation of whey derived beta-lactoglobulin, Lacprodan® BLG. (2021) - Dybdahl, Marianne; Selesko, David Benjamin; Mikkelsen, Ulla Ramer
Graphical abstract: Highlights: Lacprodan® BLG was not genotoxic when tested in a bacterial reverse mutation assay and an in vitro micronucleus assay. Exposure to Lacprodan® BLG for 90 days at up to 1000 mg/kg bw per day did not show any adverse effects in rats. The no-observed-adverse-effect level (NOAEL) in rats was 1000 mg/kg bw per day in a 90-day sub-chronic toxicity study. Abstract: The safety of Lacprodan® BLG, a whey-based protein, was evaluated with respect to genotoxicity and sub-chronic toxicity according to regulatory requirements. Lacprodan® BLG did not show any mutagenic potential in a bacterial reverse mutation assay or any clastogenic or aneugenic potential in an in vitro micronucleus assay performed in human lymphocytes. In a sub-chronic toxicity study, groups of 10 male and 10 female Wistar rats received the test item orally by gavage for 90 days at dose levels of 100, 300 and 1000 mg/kg bw/day. A control group, also including 10 male and 10 female rats, received sterile water, as vehicle. No treatment-related clinical observations or toxicological effects on body or organ weights, food consumption, ophthalmic effects, hematology, clinical chemistry, fertility, urinalysis, or pathology were identified. Therefore, the no-observed-adverse-effect level (NOAEL) for Lacprodan® BLG in the 90-day toxicity study was established as 1000 mg/kg bw/day, corresponding to the highest dose level administered.